Accounting for expenditure on software development for internal use. - Walker, R. G.; Oliver, G. R. (Abacus, 2005)
The methods accepted by Australian, International, U.S. and U.K. Accounting Standards for the treatment of expenditure on software development are inconsistent, and permissive. A host of methods for recording capitalized software in terms of those standards is identified by reference to an illustrative case study. It is questionable whether many in-house developed software applications satisfy the professionally endorsed definition of‘asset’. Moreover, even if accounting standards significantly reduce the range of options for capitalizing expenditure on software development, there would still be many values which could be assigned to capitalized software. That suggests that those‘measures’ are not reliable, so that it would be inappropriate initially to recognize software expenditure as an‘asset’. It is contended that expensing all outlays on software development as they are incurred (accompanied by reporting that expenditure as a line item in statements of financial performance, and expanded disclosures in notes) is likely to provide a clearer and more useful report on business operations than the alternative of capitalization, amortization and subsequent assessments of whether or not recorded values should be adjusted for‘impairment’.